PENGEMBANGAN BAHAN AJAR PENCEMARAN LINGKUNGAN BERBASIS PENGOLAHAN LIMBAH DI MADRASAH TSANAWIYAH SABILUL ULUM MAYONG JEPARA - Fajeri, Alif Mahbub Zainal; Irsadi, Andin; Budiyanto, Kuntoro (Journal of Biology Education, 2015)
Abstract _________________________________________________________________This study aimed to observe, analyze needs, develop, and test the feasibility, legibility, and the effectiveness of teaching materials based environmental pollution in sewage treatment MTs Sabilul Ulum Mayong Jepara. This study wasa research and development (R & D). Data feasibility of teaching materials drawn from the assessment of the validity of the experts, to test the readability of data taken from student responses after administration of teaching materials. The effectiveness of teaching materials was tested through experiments with research design Control Group Pre-test Post-test to see its effect on student learning outcomes in the study sample was taken by purposive sampling technique. The validity of the assessment results based teaching materials waste treatment by media experts 78.8% with decent criteria and 94.6% of matter experts with very decent criteria. The trial results legibility teaching materials received responses of students with a mean score of  92% and both teachers and students are very interested in the sewage treatment based teaching materials. Results of testing the use of teaching materials showed that the averag epost-test value of the experimental class 75.53 and control class 69.93. Based on the results of t-test experimental class and control class showstcount price of 4,103> ttabel price for df = 78 with a 1% significance level of 2,38. Based on the results of the study concluded that there is a very significant difference between the average value of the end of the experimental class with the control class. The results indicated that sewage treatment based teaching materials was effective for student learning outcomes.Abstrak ___________________________________________________________________ Penelitian ini bertujuan untuk mengembangkan, serta menguji kelayakan, keterbacaan, dan efektivitas bahan ajar pencemaran lingkungan  berbasis pengolahan limbah di MTs Sabilul Ulum Mayong Jepara. Penelitian ini merupakan research and development (R & D). Data kelayakan bahan ajar diambil dari penilaian validitas para pakar, untuk data uji coba keterbacaan diambil dari tanggapan siswa setelah diberikan materi bahan ajar.  Keefektifan bahan ajar diuji melalui eksperimen dengan rancangan   penelitian Control Group Pre-test Post-test untuk melihat pengaruhnya terhadap hasil belajar siswa Sampel pada penelitian ini diambil dengan teknik purposive sampling. Hasil  penilaian validitas bahan ajar berbasis pengolahan limbah oleh pakar media 78,8%  dengan kriteria layak dan pakar materi 94,6% dengan kriteria sangat layak. Hasil uji coba keterbacaan bahan ajar mendapat tanggapan siswa dengan rerata skor 92% dan  baik guru maupun siswa sangat tertarik terhadap bahan ajar berbasis pengolahan limbah. Hasil uji coba pemakaian bahan ajar  menunjukkan bahwa rerata nilai post-test kelas eksperimen 75.53  dan kelas kontrol 68,93. Berdasarkan hasil uji t kelas eksperimen dan kelas kontrol menunjukkan harga thitung sebesar 4,103 > harga ttabel untuk dk = 78 dengan taraf signifikansi 1% sebesar 2,38. Berdasarkan hasil penelitian  disimpulkan bahwa ada perbedaan yang sangat signifikan antara rata-rata nilai akhir kelas eksperimen dengan kelas kontrol. Hal ini menunjukkan  bahan ajar pencemaran lingkungan  berbasis pengolahan limbah efektif terhadap hasil belajar siswa.